The global problem of land degradation: A review - Mahata, Sangita; Sharma, Vishwambhar Nath (National Geographical Journal of India, 2022)
Land degradation has been a subject of academic research all across the world and still an important global issue in the twenty-rst century. Land is an essential non-renewable resource that is degraded day by day through some major factors like natural, anthropogenic and climatic factors. It is the principal basis for human well-being and livelihood as it provides us food, shelter, and multiple other ecosystem services. Land degradation has become a severe environmental problem. It is observed that a complex interplay between a variety of interrelated processes leads to what we dened as land degradation. It occurs in the form of deforestation, desertication, rapid changes in climatic conditions, waterlogging, salinization, erosion, and loss of organic matter components, etc. But we can save our land or manage our land from degradation by identifying sustainable land management practices and by adopting a precise methodology for assessing land degradation. The major objectives of this study are to address the problems of land degradation and to explore sustainable land management practices through different researches. This paper surveys the research works done on this theme and points out the key drivers of land degradation across the world, the social, economic and environmental costs of land degradation, the extent and severity of global land degradation and the appropriate methods for assessment of land degradation at global level and opportunities for improvement.